The Influence of Intellectual Capital, Growth Opportunity, and Profitability on Firm Value: Evidence from Telecommunications Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) During 2020–2024 - Syaira Aprilia; Leny Suzan (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study examines the influence of intellectual capital, growth opportunity, and profitability on firm value among telecommunications sub-sector companies listed on the Indonesia Stock Exchange over the 2020–2024 period. The research adopts a quantitative approach with a descriptive orientation, drawing on secondary data sourced from audited financial statements. Sample selection was carried out through purposive sampling, and hypotheses were tested using panel data regression analysis processed via EViews software. Firm value was operationalized using Tobin's Q, intellectual capital was measured through the Value Added Intellectual Coefficient (VAIC™), growth opportunity was proxied by asset growth, and profitability was assessed using Return on Assets (ROA). Partially, no significant effect, while growth opportunity has a significant negative effect, suggesting investors are concerned about investment risk and financing burdens associated with growth. Companies are encouraged to improve resource management efficiency and profitability to strengthen investor confidence and firm value.